Magnetic Control of Macromolecular Conformations in Supramolecular Anionic Polysaccharide–Iron Complexes. (18th September 2015) - Schefer, Larissa; Bulant, Ariane; Zeder, Christophe; Saha, Abhijit; Mezzenga, Raffaele
Abstract: The anionic iota carrageenan polysaccharide is enriched with Fe II and Fe III by ion exchange against FeSO4 and FeCl3 . With divalent iron, portions of polymer chains undergo a secondary structure transition from random coils to single helices. The single‐chain macromolecular conformations can be manipulated by an external magnetic field: upon exposure to 1.1 T, the helical portions exhibit 1.5‐fold stiffening and 1.1‐fold stretching, whereas the coil conformations respond much less as a result of lower contents of condensed iron ions. Along with the coil–helix transition, the trivalent iron triggers the formation of superstructures. The applicability of iron‐enriched iota carrageenan as functional ingredient for food fortification is tested by free Fe 2+ and Fe 3+ contents, respectively, with the most promising iota‐Fe III yielding 53 % of bound iron, which is due to the superstructures, where the ferric ions are chelated by the supramolecularly self‐assembled polymer host.